Use of population based background rates of disease to assess vaccine safety in childhood and mass immunisation in Denmark: nationwide population based cohort study. (17th September 2012) - Rasmussen, Thomas A; Jørgensen, Martin R S; Bjerrum, Stephanie; Jensen-Fangel, Søren; Støvring, Henrik; Østergaard, Lars; Søgaard, Ole S
Abstract : Objectives To predict the number of selected outcomes temporally associated but not caused by vaccination, to aid causality assessment of adverse events arising after mass immunisation in a paediatric population. Design Nationwide population based cohort study. Setting Denmark. Participants All liveborn infants delivered after 1 January 1980. Study population was followed from date of birth until hospital admission for selected outcome diagnoses, death, first emigration, age 18 years, or 31 December 2009. The study population was subject to vaccines used in standard childhood immunisation in Denmark, with 82-93% vaccine coverage. Main outcome measures Incidence of acute infectious and post-infectious polyneuritis (Guillain-Barré syndrome), acute transverse myelitis, optic polyneuritis, facial nerve palsy, anaphylactic shock, seizure, multiple sclerosis, autoimmune thrombocytopenia, type 1 diabetes mellitus, juvenile and rheumatoid arthritis, narcolepsy, and death of unknown cause stratified by sex, age, and season. We predicted the number of events for a hypothetical vaccine cohort of 1 000 000 people for follow-up periods of up to 182 days. Results The study included 2 300 227 liveborn infants, yielding 37 262 404 person years of follow-up; median follow-up was 16.8 person years. Incidence of outcome diagnoses spanned from 0.32 per 100 000 patient years for autoimmune thrombocytopenia to 189.82 per 100 000 patient years for seizure. Seasonal differences were most pronounced for anaphylactic shock, seizure, and multiple sclerosis. Even for rare outcomes, numerous events were predicted in the hypothetical vaccine cohort. We predicted that 20 cases of type 1 diabetes mellitus, 19 of juvenile or rheumatoid arthritis, eight of facial nerve palsy, and five of multiple sclerosis per 1 000 000 children would occur within 42 days after vaccination. Conclusions Incorporating exact background rates of disease based on age, sex, and seasonal distribution could strengthen vaccine safety assessment, and provides an evidence based focus for discussing the incremental risk of newly introduced vaccines.